Antimicrobial effectiveness of bioactive packaging materials from edible chitosan and casein polymers: assessment on carrot, cheese, and salami - Moreira, Maria del Rosario (2011)
Antimicrobial packaging is one of the most promising active packaging systems for controlling spoilage and pathogenic microorganisms. In this work, the intrinsic antimicrobial properties of chitosan (CH) were combined with the excellent thermoplastic and film-forming properties of sodium caseinate (SC) to prepare SC/CH film-forming solutions and films. The antimicrobial effectiveness of SC, CH and SC/CH coatings on the native microfloras of cheese, salami and carrots was evaluated. In vitro assays indicated that the most significant antimicrobial effect were achieved by CH and SC/CH solutions/films on Cheddar cheese and salami microfloras; at 5 days storage, the higher antimicrobial retention was observed at 65% RH in both temperatures (10ºC and 20ºC). However, SC (coating and film) did not exert antimicrobial activity on any of the native microfloras studied and no significant antimicrobial effects were observed on the carrot microflora when the CH and SC/CH film-forming solutions were used. In vivo assays were also performed with SC, CH and SC/CH applied as film-forming solutions (coatings) or wrappers on the three food substrates. CH and SC/CH applied at both immersion and wrapper exerted a strong bactericidal action on the three microbial populations analyzed with reductions of 2 to 4.5 order log. An improvement of the bactericidal properties of the CH/SC blend respect to those of the neat CH film is reported. The ionic interaction between both macromolecules enhances its antimicrobial properties.